Association of Albuminuria and Oxygen Saturation in Patients with COPD: A Cross-Sectional Study - Niraj Bam; Satish Das; Bibek Shrestha; Nabin Ayer; Milan Pokhrel (Janaki Medical College Journal of Medical Science, 2025)
Background & Objectives: Chronic Obstructive Pulmonary Disease (COPD) is a leading cause of morbidity and mortality, often complicated by comorbidities such as cardiovascular disease. Albuminuria, assessed by urine albumin-to-creatinine ratio (UACR), is a marker of endothelial dysfunction and adverse outcomes. This study aimed to investigate the prevalence of albuminuria in COPD patients and its association with oxygenation status and disease severity.Materials and Methods: A cross-sectional study was conducted among 70 COPD patients at Tribhuvan University Teaching Hospital, Kathmandu. UACR was measured from spot urine samples, and patients were classified into GOLD groups (A–D). Arterial partial pressure of oxygen (PaO₂) was obtained via arterial blood gas analysis, and peripheral oxygen saturation (SpO₂) was measured by pulse oximetry. Statistical analysis was performed using SPSS.Results: Among the participants, 42.9% had normal UACR, 52.9% had microalbuminuria, and 4.3% had macroalbuminuria. The prevalence of albuminuria was higher in GOLD Group D patients (67.5%). Patients with albuminuria had lower mean PaO₂ compared to those without, indicating an association between hypoxemia and higher UACR values (p=0.042).Conclusion: Albuminuria is common in COPD patients and is associated with both greater disease severity and lower oxygen levels. Screening for albuminuria may help identify high-risk COPD patients for earlier cardiovascular and renal risk management.